An update on Burkholderia pseudomallei infection: epidemiology, pathogenesis, diagnostic approaches and treatment challenges: An update on Burkholderia pseudomallei infection - Mazhar, Ishad; Andalib, Sofia; Alim, Rumana; Munwar, Shaila (Journal of the Medical College for Women & Hospital, 2025)
The discovery of emerging organisms is the interesting part of medical science. Burkholderia pseudomallei are the etiological agent of melioidosis, which can be a fatal disease due to high mortality rate and relapse rate. The two primary endemic zones are northern Australia and Southeast Asia, however, B. pseudomallei are found throughout the tropics. In addition, variable clinical presentation, pre-existing comorbidity, low awareness, and lack of diagnostic facilities are the contributing factors associated with disease severity. Despite notable progress in laboratory detection methods and treatment, B. pseudomallei continue to be a major global concern. Developing further successful disease diagnosis and preventive measures require an understanding of the organism's origin, transmission pathways, virulence factors and their roles in pathogenic mechanisms in human hosts. In this review, current knowledge of B. pseudomallei are discussed focusing on the epidemiology, transmission, risk factors, pathogenesis, clinical manifestations, available diagnostic methods, and antimicrobial drugs of B. pseudomallei. J Med Coll Women Hosp.2025; 21 (1):100-106